2020
DOI: 10.1097/njh.0000000000000696
|View full text |Cite
|
Sign up to set email alerts
|

The “PalliActive Caregivers” Intervention for Caregivers of Patients With Cancer in Palliative Care

Abstract: This pilot study aimed to assess the feasibility and possible effects of the “PalliActive Caregivers,” nursing intervention, on the uncertainty in illness and quality of life of family caregivers of patients with cancer receiving palliative care. This pilot study used a randomized controlled design. The participants were 80 family caregivers. The experimental group received the novel “PalliActive Caregivers” intervention. Data were collected using a sociodemographic form, the Uncertainty in Illness Scale, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…A total of 12 193 unique references were screened and 314 full-text articles were assessed; of these, 56 articles ( 41-96 ) reporting on outcomes of 49 trials for 8554 caregivers were ultimately included ( Figure 1 ). Of the 49 included trials, 34 (69%) included caregivers of patients with mixed solid tumor malignancies, 6 (12%) only lung cancer ( 42 , 59-62 , 69 , 72 , 81 ), 1 (2%) breast cancer ( 74 ), 1 (2%) pancreatic cancer ( 94 ), 1 (2%) high-grade glioma ( 43 ), 2 (4%) gastrointestinal cancers ( 73 , 76 ), and 4 (8%) hematological malignancies ( 44 , 49 , 80 , 84 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 12 193 unique references were screened and 314 full-text articles were assessed; of these, 56 articles ( 41-96 ) reporting on outcomes of 49 trials for 8554 caregivers were ultimately included ( Figure 1 ). Of the 49 included trials, 34 (69%) included caregivers of patients with mixed solid tumor malignancies, 6 (12%) only lung cancer ( 42 , 59-62 , 69 , 72 , 81 ), 1 (2%) breast cancer ( 74 ), 1 (2%) pancreatic cancer ( 94 ), 1 (2%) high-grade glioma ( 43 ), 2 (4%) gastrointestinal cancers ( 73 , 76 ), and 4 (8%) hematological malignancies ( 44 , 49 , 80 , 84 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 49 included trials, 34 (69%) included caregivers of patients with mixed solid tumor malignancies, 6 (12%) only lung cancer ( 42 , 59-62 , 69 , 72 , 81 ), 1 (2%) breast cancer ( 74 ), 1 (2%) pancreatic cancer ( 94 ), 1 (2%) high-grade glioma ( 43 ), 2 (4%) gastrointestinal cancers ( 73 , 76 ), and 4 (8%) hematological malignancies ( 44 , 49 , 80 , 84 ). A total of 32 (65%) trials were conducted in an outpatient setting ( 42-45 , 53-57 , 59-77 , 81-83 , 85 , 87 , 88 , 91 , 92 , 94 ), 5 (10%) in a home setting ( 46-48 , 51 , 78 , 79 , 86 ), 4 (8%) in an inpatient setting ( 41 , 80 , 84 , 96 ), and 8 (16%) in mixed settings ( 49 , 50 , 52 , 58 , 89 , 90 , 93 , 95 ). Of the trials, 28 were conducted in the United States ( 44 , 45 , 49-51 , 53 , 55 , 59-68 , 71-77 , 83-86 , 89 , 92 , 94 , 95 ); 4 each in Australia ( 46-48 , 52 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study involving caregivers reported that both caregiver support and emotional support were associated with positive family relationships, namely the level of social support became higher as the family became more functional [32]. There was a significant decrease in the psychological well-being and the quality of life among caregivers receiving the nursing initiative called "Palliative Care Caregivers" [33]. This result is thought to have an impact on the care burden.…”
Section: Discussionmentioning
confidence: 99%